The Impact of Inflation on Afghanistan’s Economic Growth (2005-2023) - Fetnat, Mohammad Omid; Yoldash, Nematullah (Integrated Journal for Research in Arts and Humanities, 2024)
Inflation is a crucial economic indicator impacting the stability and growth of economies, particularly in developing countries like Afghanistan. This study investigates the impact between inflation and economic growth in Afghanistan from 2005 to 2023, providing insights for policymakers. The research aims to understand both short-term and long-term impacts of inflation on economic growth, incorporating variables such as exchange rates and population. Using the Auto Regressive Distributed Lag (ARDL) model, the study finds no significant long-term impact between inflation and economic growth. However, a positive short-term impact exists, suggesting that moderate inflation can stimulate economic activity. Conversely, population growth negatively impacts long-term economic growth due to high dependency ratios and limited resources. Exchange rate fluctuations also negatively affect growth, given Afghanistan's import dependence. The study concludes that stabilizing exchange rates and managing population growth are critical for fostering long-term economic stability and growth in Afghanistan.